Toddler mental health: The Brief Child and Family Intake and Outcomes System. (November 2020) - Niccols, Alison; Cunningham, Charles; Pettingill, Peter; Bohaychuk, Donna; Duku, Eric
Despite the availability of effective early interventions, few toddlers with emotional and behavioral issues receive these services. This situation exists partly due to challenges in the identification of mental health issues in young children. We developed the Brief Child and Family Intake and Outcomes System for toddlers, which is a 36-item standardized online parent questionnaire including two externalizing scales (Cooperating; Regulating Attention, Impulsivity, and Activity), two internalizing scales (Expressing Emotion; Responding to Change), and two regulatory scales (Eating; Sleeping). We conducted a normative study of 500 Canadian children 18–36 months old, stratified by sex, age, geographic region, and parents' marital status, income, and education. Confirmatory factor analyses demonstrated good model fit, and the relationship between items and scales did not vary significantly between boys and girls or between younger and older toddlers. Reliability estimates indicated high internal consistency. Providing preliminary evidence of validity, scale scores had positive relations with measures of family distress, caregiver mood, and demographic risk variables. Analyses of latent variables revealed good evidence of discriminant validity of the scales. We extend earlier work by including scales particularly relevant to toddler emotional and behavioral regulation while at the same time minimizing respondent burden and providing norms for Canadian toddlers. The questionnaire could be used in children's mental health settings, primary care, child welfare, and daycare facilities, for intake, triage, and describing toddlers.